Changing Patterns of Homicide and Social Policy in Philadelphia, Phoenix, and St. Louis, 1980-1994 - Zahn, Margaret A. ([Verlag nicht ermittelbar], 1999)
This study sought to assess changes in the volume and types of homicide committed in Philadelphia, Phoenix, and St. Louis from 1980 to 1994 and to document the nature of those changes. Three of the eight cities originally studied by Margaret Zahn and Marc Riedel (NATURE AND PATTERNS OF HOMICIDE IN EIGHT AMERICAN CITIES, 1978 [ICPSR 8936]) were revisited for this data collection. In each city, police records were coded for each case of homicide occurring in the city each year from 1980 to 1994. Homicide data for St. Louis were provided by the St. Louis Homicide Project with Scott Decker and Richard Rosenfeld as the principal investigators. Variables describing the event cover study site, year of the case, date and time of assault, location of fatal injury, method used to kill the victim, and circumstances surrounding the death. Variables pertaining to offenders include total number of homicide and assault victims, number of offenders arrested, number of offenders identified, and disposition of event for offenders. Variables on victims focus on whether the victim was killed at work, if the victim was using drugs or alcohol, the victim's blood alcohol level, and the relationship of the victim to the offender. Demographic variables include age, sex, race, and marital status of victims and offenders.